A lithium zirconate material and its preparation method and application
By adding sintering agent fluoride to the solid phase sintering preparation of lithium zirconate materials and performing crystallization and crushing treatment, the problems of difficult to obtain high-temperature energy consumption and pure phase are solved, and the low-temperature preparation of lithium zirconate materials are achieved and Industrial production, suitable for lithium-ion batteries and other applications.
Patent Information
- Application Number
- CN202310126773.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-16
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2043-02-16
AI Technical Summary
The synthesis temperature in the solid-phase sintering preparation process of existing lithium zirconate materials is relatively high, the energy consumption is large, and it is difficult to obtain pure phase materials, which limits its industrial mass production.
By adding sintering agent fluoride to the zirconium source material and lithium source material, mixing evenly in a high-speed mixer, performing crystallization and crushing treatment, reducing the synthesis temperature, and obtaining a pure phase lithium zirconate material.
The synthesis temperature of lithium zirconate material has been successfully reduced, the preparation process has been simplified, its industrial production has been realized, and pure phase materials have been obtained, which are suitable for lithium-ion batteries and other applications.
Smart Images

Figure CN116119711B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion battery materials, and in particular to a lithium zirconate material and a preparation method and application thereof. Background Art
[0002] Lithium-rich manganese-based layered oxide cathode materials have attracted great attention in recent years due to their excellent capacity (>250mAh / g) and energy density (>1000wh / kg). During the charge and discharge process, lithium-rich materials can provide sufficient lithium ions as a lithium source in a low-lithium state, thereby increasing the specific capacity.
[0003] Lithium zirconate materials are a type of material with excellent thermal stability and high lithium ion transmission performance. In addition, lithium zirconate materials can also be used to absorb CO2 at high temperatures. For example, Japanese patent (JP999214, 1997) discloses a lithium zirconate material that absorbs CO2 gas at high temperatures. This lithium zirconate material absorbs CO2 at around 550°C and desorbs it at around 700°C. Lithium zirconate materials can also be used as modifying materials to modify positive electrode materials to improve the electrochemical properties of the materials. For example, Chinese patent CN103400982A discloses a nano-lithium zirconate-modified lithium iron phosphate composite material to obtain a lithium iron phosphate material with high conductivity, excellent rate and low temperature performance, and good cycle performance.
[0004] Therefore, it is of great significance to develop and study the preparation method of lithium zirconate. There are many methods for synthesizing lithium zirconate, and the commonly used synthesis methods include solid-phase sintering method, precipitation method and sol-gel method. Among them, the reaction rate and conditions in the precipitation method are difficult to control, and it is not easy to obtain pure and uniform lithium zirconate particles. The gel used in the sol-gel method is expensive and it is not easy to achieve its mass industrial production. The solid-phase method has a simple preparation process and is easy to achieve industrial mass production, but the current synthesis temperature of lithium zirconate prepared by solid-phase sintering is relatively high, and the energy consumption is large; the prepared phase is impure, and mass production is difficult. Summary of the invention
[0005] The embodiments of the present invention provide a lithium zirconate material and a preparation method and application thereof. The lithium zirconate material is synthesized by adding a sintering aid fluoride, reducing the particle size of the zirconium source and changing the mixing method. The X-ray diffraction peak of the lithium zirconate material meets the standard card number 75-2157 and no impurity peaks are generated, indicating that a pure phase lithium zirconate material is successfully prepared. The preparation method provided by the present invention uses a sintering aid fluoride, which reduces the synthesis temperature of the lithium zirconate material prepared by the solid phase method. The preparation method is simple and easy to industrialize the production of lithium zirconate.
[0006] In a first aspect, an embodiment of the present invention provides a method for preparing a lithium zirconate material, the preparation method comprising:
[0007] Weigh the lithium source material and the zirconium source material according to the stoichiometric ratio, put them in a high-speed mixer, add a sintering aid and mix them evenly to obtain a mixed material;
[0008] The mixed material is crystallized at a temperature of 750° C. to 900° C. for a time of 5 hours to 15 hours to obtain a precursor material;
[0009] The precursor material is crushed to obtain a lithium zirconate material;
[0010] Wherein, the particle size Dv50 of the zirconium source material is between 0.5 μm and 3 μm;
[0011] The sintering aid is a fluoride;
[0012] The rotation speed of the high-speed mixer is between 2000 rpm and 3500 rpm, and the mixing time is between 5 min and 30 min.
[0013] Preferably, the zirconium source material includes: one or more of zirconium oxide, zirconium nitrate or zirconium hydroxide;
[0014] The lithium source material comprises: one or more of lithium carbonate, lithium hydroxide, lithium nitrate and lithium acetate; the amount of the lithium source material is 2%-10% in excess of the stoichiometric amount.
[0015] Preferably, the zirconium source material is zirconium oxide; and the lithium source material is lithium carbonate.
[0016] Preferably, the mass percentage of the sintering aid to the mixed material is 0.5%-2%.
[0017] Preferably, the fluoride comprises ammonium fluoride and / or aluminum fluoride.
[0018] Preferably, the crushing method comprises:
[0019] The precursor material is primarily crushed by a jaw crusher and a roller crusher in sequence to obtain a coarse particle powder material with a particle size Dv50 of 15 μm-50 μm;
[0020] The coarse-grained powder material is crushed by a disc jet mill to obtain a lithium zirconate material with a particle size Dv50 of 1 μm-5 μm.
[0021] In a second aspect, an embodiment of the present invention provides a lithium zirconate material prepared by the preparation method described in the first aspect above, wherein the chemical formula of the lithium zirconate material is Li2ZrO3, the color is white, and the pH value is between 10-12.
[0022] Preferably, the lithium zirconate material is a pure phase material, and the diffraction peak conforms to the standard card number 75-2157.
[0023] In a third aspect, an embodiment of the present invention provides a lithium-ion battery, wherein the lithium-ion battery comprises the lithium zirconate material described in the second aspect.
[0024] The embodiment of the present invention provides a lithium zirconate material and a preparation method and application thereof. The method comprises placing a lithium source material and a zirconium source material in a high-speed mixer, adding a sintering aid fluoride and mixing them at a high speed, and finally obtaining a pure-phase lithium zirconate material after crystallization and crushing. The particle size Dv50 of the zirconium source material used in the embodiment of the present invention is between 0.5 μm and 3 μm. Since the relative atomic mass of zirconium is heavier than that of lithium, the use of a zirconium source material with a smaller particle size can improve the reaction activity, which is beneficial to combining lithium and zirconium to form lithium zirconate, shortening the synthesis time, and further reducing the preparation cost.
[0025] The preparation method provided by the invention adopts fluoride as a sintering aid, thereby reducing the synthesis temperature of the lithium zirconate material prepared by the solid phase method. The preparation method is simple and is easy for the industrial production of lithium zirconate. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] The technical solution of the embodiment of the present invention is further described in detail below through the drawings and examples.
[0027] Figure 1 is a flow chart of a method for preparing a lithium zirconate material provided in an embodiment of the present invention;
[0028] Figure 2 1 is an X-ray diffraction (XRD) diagram of the lithium zirconate material provided in Example 1, Example 2 and Example 3 of the present invention. DETAILED DESCRIPTION
[0029] The present invention is further described in detail below through the accompanying drawings and specific embodiments, but it should be understood that these embodiments are only used for more detailed description and should not be understood as limiting the present invention in any form, that is, they are not intended to limit the protection scope of the present invention.
[0030] The present invention provides a method for preparing a lithium zirconate material. Figure 1 As shown, the preparation method comprises:
[0031] Step 110, weighing a lithium source material and a zirconium source material according to a stoichiometric ratio, placing them in a high-speed mixer, adding a sintering aid and mixing them evenly to obtain a mixed material;
[0032] The zirconium source material includes: one or more of zirconium oxide, zirconium nitrate or zirconium hydroxide, preferably zirconium oxide; the particle size Dv50 of the zirconium source material is between 0.5 μm and 3 μm;
[0033] The lithium source material includes: one or more of lithium carbonate, lithium hydroxide, lithium nitrate, and lithium acetate, preferably lithium carbonate; the amount of the lithium source material is 2%-10% in excess according to the stoichiometric amount;
[0034] The sintering aid is a fluoride, including ammonium fluoride and / or aluminum fluoride, and the mass of the sintering aid fluoride accounts for 0.5%-2% of the total mass of the mixed material;
[0035] In the present application, during the experimental process of synthesizing lithium zirconate material, it was found that adding fluoride can reduce the synthesis temperature. Therefore, using fluoride as a sintering aid can help reduce the synthesis temperature of lithium zirconate and reduce energy consumption.
[0036] The speed of the high-speed mixer is between 2000 rpm and 3500 rpm, and the mixing time is between 5 min and 30 min.
[0037] Step 120, crystallizing the mixed material at a crystallization temperature of 750° C. to 900° C. for a crystallization time of 5 hours to 15 hours to obtain a precursor material.
[0038] Step 130, crushing the precursor material to obtain a lithium zirconate material;
[0039] Specifically, the crushing method includes: using a jaw crusher and a roller mill to perform primary crushing on the precursor material in sequence to obtain a coarse-grained powder material with a particle size Dv50 of 15μm-50μm; crushing the coarse-grained powder material by a disc air jet mill to obtain a lithium zirconate material with a particle size Dv50 of 1μm-5μm.
[0040] The embodiment of the present invention provides a lithium zirconate material prepared by the above preparation method. The chemical formula of the lithium zirconate material is Li2ZrO3, the color is white, and the pH is between 10-12; the lithium zirconate material is a pure phase material, and the diffraction peak meets the standard card number 75-2157.
[0041] The lithium zirconate material prepared by the above preparation method in the embodiment of the present invention can be used as an active material or a modifying material of an active material in a lithium ion battery.
[0042] In the present application, the particle size Dv50 of the zirconium raw material is between 0.5μm and 3μm, for example, it can be 0.5μm, 1μm, 1.5μm, 2μm, 2.5μm, 3μm or any value within the range; the reason why the raw material of the zirconium raw material needs to be pretreated into a zirconium raw material fine powder with a particle size Dv50 of 0.5μm-3μm before synthesis is that since the relative atomic mass of zirconium (91.22) is heavier than the relative atomic mass of lithium (6.94), it is not conducive to the combination of the two. Therefore, the zirconium source material is made to have a smaller average particle size as much as possible through physical crushing to improve its reaction activity, thereby facilitating the combination of lithium and zirconium to form lithium zirconate.
[0043] In order to better understand the technical solution provided by the present invention, the preparation process of the lithium zirconate material of the present invention is respectively described below with specific examples.
[0044] Example 1
[0045] This embodiment provides a preparation process of a lithium zirconate material, and the specific preparation steps are as follows:
[0046] (1) 61 g of lithium carbonate and 101 g of zirconium dioxide were weighed according to the stoichiometric ratio, placed in a high-speed mixer, 0.81 g of ammonium fluoride as a sintering aid was added, the speed of the high-speed mixer was set to 3500 rpm, the mixing time was 5 min, and the mixture was mixed uniformly to obtain a mixed material;
[0047] The zirconium dioxide used in this step is obtained by crushing the raw zirconium dioxide at least 5 times with a disc airflow mill to obtain zirconium dioxide powder with a particle size Dv50 of 1.6 μm; the lithium source material lithium carbonate is in excess of 2%; the mass of the added ammonium fluoride accounts for 0.5% of the total mass of lithium carbonate and zirconium dioxide.
[0048] (2) The mixed material is loaded into a high-temperature sagger, wherein the loading amount of the mixed material in the high-temperature sagger is 70% of the volume of the sagger, and the high-temperature sagger is placed in a high-temperature furnace for crystallization treatment. Under an air atmosphere, the crystallization temperature is set to 750°C, the heating rate is 3°C / min, the crystallization time is 15 hours, and the precursor material is obtained after natural cooling.
[0049] (3) The precursor material is crushed, specifically: the sintered material is crushed by a jaw crusher and a roller mill to obtain a coarse particle powder with a particle size Dv50 of 15.8 μm, and then the coarse particle powder is crushed by a disc air flow mill. The air pressure of the disc air flow mill used is 8 MPa. After multiple air flow crushing, a powder with a particle size Dv50 of 2.5 μm is obtained to obtain a lithium zirconate material, which is white powder in color and has a tested pH of 10.5.
[0050] The XRD pattern of the lithium zirconate material prepared in this example is as follows: Figure 2As shown, it can be seen that all characteristic diffraction peaks in the figure are consistent with the characteristic peaks of lithium zirconate of standard card number 75-2157, and there are no impurity peaks, indicating that the present invention successfully prepares pure phase lithium zirconate material at low temperature.
[0051] Example 2
[0052] This embodiment provides a preparation process of a lithium zirconate material, and the specific preparation steps are as follows:
[0053] (1) 50.67 g of lithium carbonate and 221.65 g of zirconium nitrate were weighed according to the stoichiometric ratio, placed in a high-speed mixer, 5.4 g of ammonium fluoride as a sintering aid was added, the speed of the high-speed mixer was set to 2800 rpm, the mixing time was 10 min, and the mixture was mixed uniformly to obtain a mixed material;
[0054] The zirconium nitrate used in this step is obtained by crushing the raw material zirconium nitrate by a disc airflow mill to obtain zirconium nitrate powder with a particle size Dv50 of 2.1 μm; the lithium source material lithium carbonate is 5% in excess; the mass of the added ammonium fluoride accounts for 2% of the total mass of lithium carbonate and zirconium nitrate.
[0055] (2) The mixed material is loaded into a high-temperature sagger, wherein the mixed material loading amount in the high-temperature sagger is 70% of the volume of the sagger, and the high-temperature sagger is placed in a high-temperature furnace for crystallization treatment. Under an air atmosphere, the crystallization temperature is set to 800°C, the heating rate is 3°C / min, the crystallization time is 10 hours, and the precursor material is obtained after natural cooling.
[0056] (3) The precursor material is crushed, specifically: the sintered material is primarily crushed by a jaw crusher and a roller mill to obtain a coarse particle powder with a particle size Dv50 of 13.5 μm, and then the coarse particle powder is crushed by a disc air jet mill with an air pressure of 8 MPa. After multiple air jet crushing, a powder with a particle size Dv50 of 1.2 μm is obtained to obtain a lithium zirconate material, which is white powder in color and has a tested pH of 11.
[0057] The XRD pattern of the lithium zirconate material prepared in this example is as follows: Figure 2 As shown, it can be seen that all characteristic diffraction peaks in the figure are consistent with the characteristic peaks of lithium zirconate of standard card number 75-2157, and there are no impurity peaks, indicating that the present invention successfully prepares pure phase lithium zirconate material at low temperature.
[0058] Example 3
[0059] This embodiment provides a preparation process of a lithium zirconate material, and the specific preparation steps are as follows:
[0060] (1) 355 g of lithium hydroxide and 1655 g of zirconium hydroxide were weighed according to the stoichiometric ratio, placed in a high-speed mixer, 20.1 g of aluminum fluoride as a sintering aid was added, the speed of the high-speed mixer was set to 2000 rpm, the mixing time was 30 min, and the mixture was mixed uniformly to obtain a mixed material;
[0061] Among them, the zirconium hydroxide particle size Dv50 used in this step is 0.5μm, and the zirconium hydroxide raw material is subjected to three steps of sand milling-drying-air flow crushing to obtain nano-grade zirconium hydroxide fine powder, wherein the sand mill speed is 2000rmp, and zirconium beads with a particle size of 0.3mm are used; drying is carried out by spray drying to obtain zirconium hydroxide powder with uniform particle size and dispersion; finally, it is further crushed by a disc air flow mill to obtain zirconium hydroxide powder with a particle size Dv50 of 0.5μm.
[0062] The lithium source material lithium hydroxide is in excess of 10%;
[0063] The mass of the added aluminum fluoride accounts for 1% of the total mass of the lithium hydroxide and the zirconium hydroxide.
[0064] (2) The mixed material is loaded into a high-temperature sagger, wherein the mixed material loading amount in the high-temperature sagger is 70% of the volume of the sagger, and the high-temperature sagger is placed in a high-temperature furnace for crystallization treatment. Under an air atmosphere, the crystallization temperature is set to 900°C, the heating rate is 3°C / min, the crystallization time is 5 hours, and the precursor material is obtained after natural cooling.
[0065] (3) The precursor material is crushed, specifically: the sintered material is primarily crushed by a jaw crusher and a roller mill to obtain a coarse particle powder with a particle size Dv50 of 11.8 μm, and then the coarse particle powder is crushed by a disc air flow mill. The air pressure of the disc air flow mill used is 8 MPa. After multiple air flow crushing, a powder with a particle size Dv50 of 1.5 μm is obtained to obtain a lithium zirconate material, which is white powder in color and has a tested pH of 10.
[0066] The XRD pattern of the lithium zirconate material prepared in this example is as follows: Figure 2 As shown, it can be seen that all characteristic diffraction peaks in the figure are consistent with the characteristic peaks of lithium zirconate of standard card number 75-2157, and there are no impurity peaks, indicating that the present invention successfully prepares pure phase lithium zirconate material at low temperature.
[0067] The embodiment of the present invention provides a lithium zirconate material and a preparation method and application thereof. The method comprises placing a lithium source material and a zirconium source material in a high-speed mixer, adding a sintering aid fluoride and mixing them evenly at a high speed, and finally obtaining a pure-phase lithium zirconate material after crystallization and crushing. The zirconium source material used in the embodiment of the present invention requires a particle size Dv50 between 0.5 μm and 3 μm. Since the relative atomic mass of zirconium is heavier than that of lithium, the use of a zirconium source material with a smaller particle size can improve the reaction activity, which is beneficial for combining lithium and zirconium to form lithium zirconate, shortening the synthesis time, and further reducing the preparation cost.
[0068] The preparation method provided by the invention adopts fluoride as a sintering aid, thereby reducing the synthesis temperature of the lithium zirconate material prepared by the solid phase method. The preparation method is simple and is easy for the industrial production of lithium zirconate.
[0069] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for preparing a lithium zirconate material, characterized in that: The preparation method comprises: Weigh the lithium source material and the zirconium source material according to the stoichiometric ratio, put them in a high-speed mixer, add a sintering aid and mix them evenly to obtain a mixed material; The mixed material is crystallized at a temperature of 750°C and a crystallization time of 5 hours to 15 hours to obtain a precursor material; The precursor material is crushed to obtain a lithium zirconate material; Wherein, the particle size Dv50 of the zirconium source material is between 0.5 μm and 3 μm; The sintering aid is a fluoride; the fluoride includes ammonium fluoride and / or aluminum fluoride; The speed of the high-speed mixer is between 2000rpm and 3500rpm, and the mixing time is 5min to 30min; The Dv50 of the lithium zirconate material is 1 μm-5 μm; The lithium zirconate material is used as an active material or a modified material of an active material in a lithium ion battery; The lithium zirconate material is a pure phase material, and the diffraction peak conforms to the standard card number 75-2157.
2. The preparation method according to claim 1, characterized in that: The zirconium source material includes: one or more of zirconium oxide, zirconium nitrate or zirconium hydroxide; The lithium source material includes: one or more of lithium carbonate, lithium hydroxide, lithium nitrate, and lithium acetate; the amount of the lithium source material is 2%-10% in excess of the stoichiometric amount.
3. The preparation method according to claim 2, characterized in that: The zirconium source material is zirconium oxide; the lithium source material is lithium carbonate.
4. The preparation method according to claim 1, characterized in that: The mass percentage of the sintering aid to the mixed material is 0.5%-2%.
5. The preparation method according to claim 1, characterized in that: The crushing method comprises: The precursor material is primarily crushed by a jaw crusher and a roller crusher in sequence to obtain a coarse particle powder material with a particle size Dv50 of 15 μm-50 μm; The coarse-grained powder material is crushed by a disc jet mill to obtain a lithium zirconate material with a particle size Dv50 of 1 μm-5 μm.
Citation Information
Cited By
Preparation method of battery-grade lithium zirconate
CN119461474A